(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: Sleep deprivation (SD) is biological stressor that alters metabolic parameters, induced oxidative stress and lipid peroxidation. Previous studies have shown that antioxidants substances such as melatonin, tryptophan, vitamin E and vitamin C improved stress tolerance in laboratory animals. In this study, we examined the potential protective effects of administration of vitamin C on acute and chronic sleep deprivation-induced metabolic derangement. In addition, possible processes involved in vitamin C effects on acute and chronic sleep deprivation-induced metabolic derangement were determined. Thirty-five rats (120-250g) were used. The rats were divided into 7 groups of 5 rats each as Control (CTRL), Acute sleep deprived untreated with vitamin C (AC), Acute sleep deprived treated with vitamin C (AWC), Chronic sleep deprived untreated with vitamin C (CC), Chronic sleep deprived treated with vitamin C (CWC), Chronic sleep deprived + Recovery untreated with vitamin C (RC), and Chronic sleep deprived + Recovery treated with vitamin C (RWC). The SD was carried out for 20h for 1 day on the acute groups, and for 20h/day for 5 days on the chronic group, using the Multiple Modified Platforms (MMP) after oral administration of 300mg/kg of vitamin C to all vitamin C-treated groups. The recovery groups were further observed for five days after SD. The control group were treated with vitamin C and without stress in their home cages. At the end of the experiment, the animals were sacrificed and blood was collected for estimation of plasma glucose, insulin, cortisol and malondialdehyde (MDA). The results showed that acute and chronic SDs significantly (p<0.05) increased MDA and cortisol levels, while significantly (p<0.05) reduced the levels of insulin. Treatment with vitamin C reversed the changes in the MDA, cortisol and plasma insulin levels. Additionally, allowing the rats to recover for 5 days after sleep deprivation corrected the observed changes. Plasma glucose was significantly (p<0.05) reduced in all the sleep deprived groups compared to the control. In conclusion, sleep deprivation induced metabolic, hormonal and lipid peroxidation derangement, and treatment with vitamin C prevented these impairments. Thus, the effects of vitamin C could improve stress tolerance in rats.